AMERICAN PIONEER FAMILY VALUES IN LAURA INGALLS WILDER’S LITTLE HOUSE IN THE BIG WOODS - Mawikere, Pingkan Agnes; Sabudu, Delli; Lolowang, Imelda (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
American pioneers were adventurous individuals and families who migrated westward during the 19th century to settle and establish new communities in uncharted territories. American pioneers were brave and daring individuals who ventured into the unknown, seeking a better life for themselves and future generations. This qualitative research explores the of American pioneer family values in Laura Ingalls Wilder's novel, 'Little House in the Big Woods. This study aims to reveal the familial beliefs, ethics, life’s priorities and worldviews during the late 19th-century westward expansion, employing a qualitative methodology suitable for analyzing data derived from literary sources. In essence, the pioneers in this narrative provide a rich illustration for contemporary relevance, offering insights into environmental and familial harmony, and the integration of religious principles into daily life. Their story challenges us to not only reflect on the past but to actively incorporate these enduring values into our present lives, fostering a holistic and principled approach that resonates across generations.